Strategi Pengembangan Usaha Kecil Menengah Produk Olahan Coklat - Difana Meilani; Roby Febrinaldo (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
Strategic planning is an art and knowledge in formulating, implementing and evaluating crossfunctional decisions in an organization to achieve its objectives. Chokato factory is a SME which deals inthe processing of cocoa bean in to several products and the factory is facing some constraints such ashigh competition, less modal, and unmaximal promotion. Therefore, this research was carried out toformulate the right business strategy for Chokato factory. The formulation analyzed the internal andexternal factors using IFE and EFE matrix, disposition while the design of strategy alternative used IEmatrix and SWOT. From SWOT matrix obtained 15 alternative strategies. Strategy Priority is determinedusing a matrix QSP. Based on the problems that occur on the factory Chokato, the strategy to develop theplant site into a cocoa processing center and special chocolate agro tourism is the most prioritizedstrategy. Therefore, all things related to the strategy should be optimized in order to develop the factoryChokato.Keywords: strategy determination, SWOT analysis, the industry of cocoa process product